2014
DOI: 10.1002/pi.4778
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of aβ-nucleated polypropylene impact copolymer

Abstract: Abstract:The effect of a -nucleating agent ( -NA) on the properties and structure of a commercial impact polypropylene copolymer (IPC) was investigated. The effect of selected -NAs on the impact resistance, stress and strain behaviour of the IPC is reported. In addition, the IPC was fractionated according to crystallinity by preparative temperature rising elution fractionation. Fractions with varying chemical composition and crystallinity were treated with a two-component -NA to investigate the effect of the -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Besides the influence of the base polymer selected in the present work or the studies cited above, this improvement in impact energy might also be due to the presence of β‐crystals (Fig. S5 in Supporting Information) that are known for their beneficial effect on PP and, in particular, on 3D‐printed PP . Furthermore, the encapsulation of the filler by the am.PO can have resulted in the enhanced impact properties, as reported in Refs.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the influence of the base polymer selected in the present work or the studies cited above, this improvement in impact energy might also be due to the presence of β‐crystals (Fig. S5 in Supporting Information) that are known for their beneficial effect on PP and, in particular, on 3D‐printed PP . Furthermore, the encapsulation of the filler by the am.PO can have resulted in the enhanced impact properties, as reported in Refs.…”
Section: Resultsmentioning
confidence: 99%
“…The β-form of iPP (β-iPP) is a metastable crystalline phase and can only be induced under special conditions, such as by adding an active β-iPP nucleation agent, using a crystallization temperature gradient, or by applying flow on a supercooled melt. In comparison with α-iPP, β-iPP demonstrates different performance characteristics, e.g., a lower melting temperature, a lower fusion heat, and remarkably improved elongation at break and impact strength. Thus, during the past five decades many research groups have focused their interests on the β-iPP. According to an early observation of Padden and Keith, depending on the crystallization temperature, two forms of spherulitic morphology of β-iPPthe radial (β III ) and the ringed (β IV ) spherulites, both with strong negative birefringenceare involved when iPP crystallizes from the quiescent melt. Furthermore, it has been revealed that single-crystal-like hedrites formed via lamellar branching and splaying in β-iPP form act as the precursors of spherulitic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The poor flexibility and impact resistance of PP are overcome by copolymerizing PP monomers with olefin monomers or by inducing beta (β)‐phase formation in PP . The β‐phase in PP may be induced by shear or incorporating β nucleating agents . Blending PP with other polymers, such as LDPE, ethylene vinyl acetate, and rubber, is also considered an alternative way of improving both the elongation and impact strength .…”
Section: Introductionmentioning
confidence: 99%
“…However, the formation of the β ‐phase when LDPE was incorporated into PP may have also contributed to the increase in impact strength. The β ‐phase of PP has high impact strength compared with the alpha ( α ) phase . Although much has been published regarding the PP/PE blends, there are few reports that correlate the PP/LDPE blend morphology to the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%